2021
DOI: 10.1002/jdd.12859
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and characteristics of medical emergencies in an Australian dental school: A retrospective study

Abstract: Purpose/Objectives: The frequency of medical emergencies in a dental setting is relatively low. However, most dental treatment occurs outside of a hospital setting; thus the time to respond to a life-threatening situation is crucial. The aim of this study was to determine the frequency and characteristics of medical emergencies that occurred at the Griffith University Dental Clinic over a 6-year period.Methods: Data involving medical emergencies was collected at a dental school between January 2014 and Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
(90 reference statements)
0
13
0
Order By: Relevance
“…Retrospective practitioner surveys [ 3 , 22 , 23 ], and clinical records-based studies [ 4 , 5 ] indicate that some medical emergencies are more common than others in a dental office: vasovagal syncope and hypoglycemia consistently figured among the top causes of medical emergency events in the majority of these studies; allergies, postural hypotension, dehydration, hyperventilation, and foreign body ingestion were also commonly reported in these studies, albeit less commonly than syncope and hypoglycemia. However, a study from the United States with a relatively older patient population reported hypertensive crisis as the most frequent emergency [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Retrospective practitioner surveys [ 3 , 22 , 23 ], and clinical records-based studies [ 4 , 5 ] indicate that some medical emergencies are more common than others in a dental office: vasovagal syncope and hypoglycemia consistently figured among the top causes of medical emergency events in the majority of these studies; allergies, postural hypotension, dehydration, hyperventilation, and foreign body ingestion were also commonly reported in these studies, albeit less commonly than syncope and hypoglycemia. However, a study from the United States with a relatively older patient population reported hypertensive crisis as the most frequent emergency [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study from a Japanese university dental hospital, the incidence of medical emergencies was 3.7 per 100,000 patients visiting the dental outpatient department [ 4 ]. In another retrospective study from an Australian dental school, the reported incidence of medical emergencies in dental clinics was 37 per 100,000 outpatients [ 5 ]. However, the incidence of medical emergency events in dental offices of academic dental institutions of the Middle Eastern countries remains unreported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…about by the inherent stresses of oral surgery procedures (Zachar & Reher, 2022). Hence, detailed knowledge of a patient's medical history can be considered a form of risk management in itself (Patel et al, 2014).…”
mentioning
confidence: 99%